OPTIMALISASI NILAI JUAL KOMODITAS LOKAL MELALUI DIVERSIFIKASI PRODUK DAN PEMANFAATAN TEKNOLOGI TEPAT GUNA SEBAGAI MEDIA PROMOSI - Utikawati, Anggi Nur; Wulandari, Ika (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program was conducted in Rejosari Village, Semin District, Gunungkidul Regency, aiming to enhance the added value of cassava through product innovation, professional packaging, and simple digital marketing strategies. The Participatory Action Research (PAR) approach was employed to ensure active community participation throughout the process. The results show that transforming raw cassava into ready-to-eat snacks such as “Si Gori” increased its market value up to tenfold. The use of paper box packaging successfully improved the product’s modern and hygienic image, while promotion via WhatsApp Story proved to be an effective, low-cost, and accessible marketing medium. The synergy between product innovation, professional packaging, and simple digital marketing created a new, sustainable micro-business model for rural communities. This program not only increased income but also fostered entrepreneurship and improved local digital literacy.